Currarino Triad: Importance of Preoperative Magnetic Resonance Imaging - AbouZeid, Amr AbdelHamid; Mohammad, Shaimaa Abdelsattar; Seada, Mohammad; Khiamy, Khaled; Gamal, Radwa (European Journal of Pediatric Surgery Reports, 2019)
Currarino triad is a rare syndrome that may be occasionally encountered during managing cases of anorectal anomalies. The triad consists of anorectal anomaly, sacral bony defect, and a presacral mass. It may be familial or sporadic, with a reported female predominance. Identification of the characteristic notched sacrum (sacral scimitar) in plain X-ray (anteroposterior view) is considered the key for the diagnosis; however, not infrequently, this radiological sign is overlooked, especially with a small sacral defect.Excision of the presacral cyst is usually performed concomitantly during anorectoplasty. The prone position is the standard approach for posterior sagittal anorectoplasty (PSARP) in males; however, in females, the supine position can be used as an alternative (anterior sagittal anorectoplasty). In this case report, excision of the presacral cyst took place in two steps: the first excision during the PSARP procedure in the prone position, and a second operation in the supine lithotomy position to remove a residual component of the lesion that was missed during the primary operation. It was clear that the supine lithotomy position provided better access to explore the presacral space than the prone position, especially with a deeply located cyst as in our case. The role of magnetic resonance imaging (MRI) in the identification of the exact nature and extent of the lesion before surgery is crucial and should be performed in all cases.
Keywords: Currarino triad; presacral cyst; anorectal malformation; MRI